Determinants of Road Traffic Accidents in Amhara Regional State, Ethiopia: Application of Binary Logistic Regression Analysis - Haile Mekonnen Fenta; Demeke Lakew workie; Essey Kebede Muluneh (International Journal of Mathematics And its Applications, 2017)
The incidence of deaths and injuries as a result of road traffic accidents is now a serious problem in Ethiopia. This study was aimed at determining the significant factors contributing to road traffic accidents in Amhara regional state, Ethiopia. A retrospective record was analyzed on the fourteen year trends of road traffic accidents in Amhara Regional State, Ethiopia, reported from 2003 to 2015 by selecting a simple random sample of 286 accidents files. Logistic regression methods were used to analyze the data and a total of 1003 accidents were registered in the selected files. Of these, 356 (35.5 %) were deaths and 647 (64.5 %) were injuries. It was found that out of 356 deaths, the majority, 286 (80.33 %) were caused by drivers who didn't use seat belt when the accident occurred. Most of the accidents, 454 (45.4 %) were caused by Cargo vehicles. Specifically in Bahir Dar city, where motorized three-wheeler are the main means of transportation, 42.1 percent of the accidents were directly or indirectly attributed to those vehicles.The regression model showed that use of seat belt, place of accident, types of vehicle and types of causes of the accident were significant contributors of road traffic accidents.Traffic accidents were increasing and use of seat belt, zone, and types of vehicle and cause of accident were significant factors that affect the occurrences of road traffic accidents.